One‐Step Stereoselective Synthesis of Trisubstituted Monofluoroalkenes from 3, 3, 3‐Trifluoropropionates. Issue 21 (13th June 2013) - Lecea, Mercedes; Grassin, Adrien; Ferreiro‐Mederos, Leticia; Choppin, Sabine; Urbano, Antonio; Carreňo, M. Carmen; Colobert, Françoise
Abstract: Stereoselective synthesis of ( E )‐monofluoroalkenes was achieved in one step by condensation of organolithium or Grignard reagents with 3, 3, 3‐trifluoropropionates. Highly functionalized monofluoroalkenes were obtained in good to excellent yields and stereoselectivities. Abstract : ( E )‐Monofluoroalkenes were obtained in good yields and stereoelectivities by condensation of organolithium or Grignard reagents to methyl or benzyl 3, 3, 3‐trifluoropropionate.